Vegetation over the last glacial maximum at Girraween Lagoon, monsoonal northern Australia. (July 2021) - Rowe, Cassandra; Wurster, Christopher M.; Zwart, Costijn; Brand, Michael; Hutley, Lindsay B.; Levchenko, Vladimir; Bird, Michael I.
Abstract: Northern Australia is a region where limited information exists on environments at the last glacial maximum (LGM). Girraween Lagoon is located on the central northern coast of Australia and is a site representative of regional tropical savanna woodlands. Girraween Lagoon remained a perennial waterbody throughout the LGM, and as a result retains a complete proxy record of last-glacial climate, vegetation and fire. This study combines independent palynological and geochemical analyses to demonstrate a dramatic reduction in both tree cover and woody richness, and an expansion of grassland, relative to current vegetation at the site. The process of tree decline was primarily controlled by the cool-dry glacial climate and CO2 effects, though more localised site characteristics restricted wetland-associated vegetation. Fire processes played less of a role in determining vegetation than during the Holocene and modern day, with reduced fire activity consistent with significantly lower biomass available to burn. Girraween Lagoon's unique and detailed palaeoecological record provides the opportunity to explore and assess modelling studies of vegetation distribution during the LGM, particularly where a number of different global vegetation and/or climate simulations are inconsistent for northern Australia, and at a range of resolutions.